Analisis Pengaruh Risiko Kredit dan Risiko Operasional Terhadap Profitabilitas Bank - Utami, Utami; Silaen, Uluan (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
Banks are business entities that collect funds from the public in the form of deposits and channel them to the public in the form of credit and / or other forms of improving the standard of living of the people. This study aims to determine the effect of credit risk and operational risk on profitability. Profitability ratios measured using return on asset assets and credit risk and operational risk are measured by non-performing loans (NPL) and BOPO. Data obtained from published financial statements published by Bank Indonesia with a period of time from 2008 to 2017. The sampling technique used in this study was purposive sampling. The number of samples is 3 banking companies listed on the Indonesia Stock Exchange. The analytical method that will be used in this study is multiple linear regression to obtain a comprehensive picture of the relationship between one variable and another. Based on hypothesis testing using statistical t test and f test the results of the research show that Non Performing Loans (NPL) have a significant effect on Profitability, while BOPO does not have a significant effect on Profitability and simultaneously there is a significant influence of Non Performing Loans (NPL) and BOPO on Profitability. Keywords: Non Performing Loan (NPL), BOPO and Return on Assets (ROA)